2022
DOI: 10.15252/embr.202153492
|View full text |Cite
|
Sign up to set email alerts
|

PWWP2B promotes DNA end resection and homologous recombination

Abstract: Genome instability is one of the leading causes of gastric cancers. However, the mutational landscape of driver genes in gastric cancer is poorly understood. Here, we investigate somatic mutations in 25 Korean gastric adenocarcinoma patients using whole-exome sequencing and show that PWWP2B is one of the most frequently mutated genes. PWWP2B mutation correlates with lower cancer patient survival. We find that PWWP2B has a role in DNA doublestrand break repair. As a nuclear protein, PWWP2B moves to sites of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Moreover, a study investigating other DDR-associated genes utilized whole exome sequencing (WES) and bioinformatics tools, revealing that PWWP (Pro-Trp-Trp-Pro) domain containing 2B (PWWP2B) is among the frequently mutated genes in tissues of Korean patients with gastric adenocarcinoma [104]. PWWP2B plays a crucial role in DDR and homologous recombination-mediated DSB repair through its interaction with ubiquitin-like with PHD and RING finger domains1 (UHRF1).…”
Section: Homologous Recombination Deficiency In Gcmentioning
confidence: 99%
“…Moreover, a study investigating other DDR-associated genes utilized whole exome sequencing (WES) and bioinformatics tools, revealing that PWWP (Pro-Trp-Trp-Pro) domain containing 2B (PWWP2B) is among the frequently mutated genes in tissues of Korean patients with gastric adenocarcinoma [104]. PWWP2B plays a crucial role in DDR and homologous recombination-mediated DSB repair through its interaction with ubiquitin-like with PHD and RING finger domains1 (UHRF1).…”
Section: Homologous Recombination Deficiency In Gcmentioning
confidence: 99%
“…DNA end resection has a critical role in the initiation of double strand breaks ends for efficient homologous recombination repair, regulating DNA damage repair and cell radiosensitivity [16][17][18][19]. Previous studies suggested that DNA end resection factors regulated the generation of ssDNA fragments and initiation of innate immune responses [20,21].…”
Section: Samhd1 Silencing Caused Cytosolic Ssdna Accumulation In Luadmentioning
confidence: 99%